KONSEP POLIGAMI DALAM PERSPEKTIF ISLAM - Hadi Wibowo; Dikdik Permana Wigandi (Yayasan Akrab Pekanbaru, 2019)
Marriage is a physical and spiritual bond between a man and a woman to live together. Polygamy is something that is currently still a pros and cons in society. This is due to differences in opinions / views of the community. Data collection techniques use library studies obtained from books, websites and other journals. This research method uses qualitative research methods. This method the authors take because qualitative research can be done by the author in the field of social science. The results of the study included the grace and mercy of Allah SWT when the Prophet Muhammad saw real practice of polygamy because the purpose of the Islamic Sharia was indeed intended to regulate human life.